2019
DOI: 10.1016/s2214-109x(19)30405-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating malaria burden among pregnant women using data from antenatal care centres in Tanzania: a population-based study

Abstract: Background More timely estimates of malaria prevalence are needed to inform optimal control strategies and measure progress. Since 2014, Tanzania has implemented nationwide malaria screening for all pregnant women within the antenatal care system. We aimed to compare malaria test results during antenatal care to two population-based prevalence surveys in Tanzanian children aged 6-59 months to examine their potential in measuring malaria trends and progress towards elimination.Methods Malaria test results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 18 publications
1
62
0
Order By: Relevance
“…In these countries, whilst more than 80% of pregnant women would make at least one ANC visit, their adherence to subsequent visits for the recommended IPTp 3+ policy ( WHO, 2014 ) remains poor ( WHO, 2015 ), with only 24% making their first ANC visit during the first trimester ( Mgata and Maluka, 2019 ; Chimatiro et al, 2018 ). Several studies have suggested pregnant women attending their first ANC could provide data as proxy for malaria transmission or as sentinel population for malaria surveillance ( van Eijk et al, 2015 ; Kitojo et al, 2019 ; Brunner et al, 2019 ). However, the same studies reports some shortfalls in using ANC data such as variation in sensitivity at different endemicities, suggesting ANC data was particularly useful for monitoring in areas approaching elimination ( Kitojo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In these countries, whilst more than 80% of pregnant women would make at least one ANC visit, their adherence to subsequent visits for the recommended IPTp 3+ policy ( WHO, 2014 ) remains poor ( WHO, 2015 ), with only 24% making their first ANC visit during the first trimester ( Mgata and Maluka, 2019 ; Chimatiro et al, 2018 ). Several studies have suggested pregnant women attending their first ANC could provide data as proxy for malaria transmission or as sentinel population for malaria surveillance ( van Eijk et al, 2015 ; Kitojo et al, 2019 ; Brunner et al, 2019 ). However, the same studies reports some shortfalls in using ANC data such as variation in sensitivity at different endemicities, suggesting ANC data was particularly useful for monitoring in areas approaching elimination ( Kitojo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested pregnant women attending their first ANC could provide data as proxy for malaria transmission or as sentinel population for malaria surveillance ( van Eijk et al, 2015 ; Kitojo et al, 2019 ; Brunner et al, 2019 ). However, the same studies reports some shortfalls in using ANC data such as variation in sensitivity at different endemicities, suggesting ANC data was particularly useful for monitoring in areas approaching elimination ( Kitojo et al, 2019 ). Moreover, ANC malaria test-positivity cannot be used to directly predict the prevalence in other population subgroups, where complementary community-level measurements remain highly relevant ( Brunner et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanzania is one of the malaria-endemic countries with approximately 1.7 million pregnant women at high risk of malaria infection (8). The trend of malaria prevalence among pregnant women in Tanzania has been uctuating with the highest of 10.3% in 2014 and the lowest of 6.8% in 2017 (9). It was observed that despite the low prevalence of malaria in some areas such as in Zanzibar Island, 0.8% of the pregnant women had malaria parasitemia during delivery (10).…”
Section: Introductionmentioning
confidence: 99%